Flabelleforma, the correct name for Precambrian Mucorites Herman non Lindau - Doweld, Alexander B. (Phytotaxa, 2017)
The fossil generic name Flabelleforma Herman 1989 is resurrected to replace the later homonym, Mucorites Herman 1979, used for unique Precambrian hyphal fungi-like microorganisms (Bacillariobiota), which is preoccupied by Mucorites Meschinelli ex Lindau 1900. The generic name Mucorites Meschinelli 1898, proposed for putative mycelial remains from the Lower Carboniferous (Visean) deposits of Esnost (France), was not validly published due to the lack of a separate generic description; the name was validated by Lindau in 1900.